2016
DOI: 10.1002/14651858.cd004303.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for dysphagia in long-term, progressive muscle disease

Abstract: There is insufficient and low-quality RCT evidence to determine the effect of interventions for dysphagia in long-term, progressive muscle disease. Clinically relevant effects of intravenous immunoglobulin for dysphagia in inclusion body myositis can neither be confirmed or excluded using the evidence presented in this review. Standardised, validated, and reliable outcome measures are needed to assess dysphagia and any possible treatment effect. Clinically meaningful outcomes for dysphagia may require a shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 43 publications
0
37
0
2
Order By: Relevance
“…These problems result in increased mealtime with a consequent decrease in food intake, weight loss or an inability to gain weight; food inhalation into the airways with subsequent breathing problems and recurrent respiratory infections; and increased episodes of choking, coughing, and spluttering while eating resulting in embarrassment and psychological difficulties [6,12,22,23]. …”
Section: Undernutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…These problems result in increased mealtime with a consequent decrease in food intake, weight loss or an inability to gain weight; food inhalation into the airways with subsequent breathing problems and recurrent respiratory infections; and increased episodes of choking, coughing, and spluttering while eating resulting in embarrassment and psychological difficulties [6,12,22,23]. …”
Section: Undernutritionmentioning
confidence: 99%
“…Due to the muscle weakness that characterizes all NMDs, oral motor activities are impaired [1]. Furthermore, increased risk of aspiration predisposes to respiratory complications, and this is worsened by co-existing respiratory muscle weakness in patients with compromised airway defence mechanisms and severe coughing [4,23]. Dysphagia can also lead to social and psychological consequences with worsening quality of life that may be associated with loss of satiety, fear of choking, embarrassment, and social isolation secondary to coughing, spluttering, and prolonged feeding times [23].…”
Section: Dysphagiamentioning
confidence: 99%
“…Impaired swallow, also called dysphagia, is a frequent symptom in NMD that occurs in 34.9% to 80% of patients, depending on the disease age group and the severity . Prevalence in paediatric patients with neuromuscular diseases (pNMD) seems to be similar to adult patients .…”
mentioning
confidence: 99%
“…Prevalence in paediatric patients with neuromuscular diseases (pNMD) seems to be similar to adult patients . However, precise estimates of the prevalence remain difficult to determine, owing to underestimation, lack of standardized assessment procedures, and inconsistency in the definition of dysphagia, especially in children . A previous study showed that in patients with NMD the oral phase of swallowing is the most compromised, followed by the pharyngeal phase .…”
mentioning
confidence: 99%
See 1 more Smart Citation